Stand-alone mp3 decoder prototype - Comia, Alexis A. (1999)
Diamond Multimedia's Rio PMP300 is the hottest MPMAN available today. It is a portable. lightweight digital music player for mixing and storing up to 60 minutes of digital quality MP3 music download from the Internet or converted from your personal CD collection. It is smaller than an audio cassette player and it has no moving parts, so it never skips even during the most extreme activities. It is powered only by a single AA battery and can last up to 12 hours of continuous playback! Removable flash memory upgrade cards (sold separately) gives additional music storage capacity. It sells for only 199.95. As MP3's become more and more popular, the demand for MP3 players increase. We plan to build a simple MP3 decoder prototype that is capable of decoding a segment or an MP3 file downloaded from a PC using the 56002 Evaluation Module.